SCCmec Type IX Element in Methicillin Resistant Staphylococcusaureusspa Type t337 (CC9) Isolated from Pigs and Pork in Thailand - Vestergaard, Martin; Cavaco, Lina; Sirichote, Pantip; Unahalekhakac, Aekkawat; Dangsakul, Worawat; Svendsen, Christina A.; Aarestrup, Frank M.; Hendriksen, Rene (Frontiers in Microbiology, 2012)
Methicillin resistant Staphylococcus aureus (MRSA) have emerged among livestock in several countries. In this study, we describe the results of a screening performed in pigs and raw pork samples in Thailand. Ten pork samples and 15 nasal swabs from pigs were collected from two markets and one pig farm in the Samuth Songkhram province in Thailand. MRSA were isolated using selective isolation procedures and confirmed by mecA PCR. The MRSA were characterized by antimicrobial susceptibility testing, PFGE, spa typing, SCCmec typing, and MLST. Resistance and virulence markers were screened using a microarray. Five of the pork samples and six pig nasal swabs were positive for MRSA. All 11 isolates belonged to spa type t337 and CC9 but showed diversity in antimicrobial resistance patterns and PFGE profiles. All isolates harbored SCCmec IX and were resistant to seven out of 14 tested antimicrobials; additional resistances were found in the pork isolates. Microarray analysis identified blaZ, aac-aphD, vga(A), tetM, and a tet efflux marker, in all strains and additionally ermB and aadD, cat and fex(A) in the pork isolates. None of the isolates were found PVL-positive, but enterotoxins were identified in all isolates. This is, to our knowledge, the first description of MRSA in livestock and food products in Thailand and also the first observation of MRSA CC9 associated with SCCmec IX. This study indicates a likely widespread distribution of MRSA in pig and pork in Thailand and further investigation on the prevalence and importance of livestock associated MRSA in Thailand is needed.